Triphenyl phosphate induced apoptosis of mice testicular Leydig cells and TM3 cells through ROS-mediated mitochondrial fusion inhibition - Minxin Wang; Jinyu Xu; Zhengbo Zhao; Lichao Gong; Yu Su; Zhichao Fang; Pengfei Chen; Yifan Liu; Lianshuang Zhang; Feibo Xu (Ecotoxicology and Environmental Safety, 2023)
Triphenyl phosphate (TPHP) is a widely used organophosphate flame retardant and has biological toxicity. Previous studies showed TPHP can restrain testosterone biosynthesis in Leydig cells, while the underlying mechanisms remain unclear. In this study, C57BL/6J male mice were exposed to 0, 5, 50, and 200 mg/kg B.W. of TPHP for 30 d by oral, as well as TM3 cells were treated with 0, 50, 100, and 200 μM of TPHP for 24 h. Results showed that TPHP induced testes damage, including spermatogenesis disorders and testosterone synthesis inhibition. Meanwhile, TPHP can cause apoptosis in testicular Leydig cells and TM3 cells, as evidenced by the increased apoptosis rate and decreased Bcl-2/Bax ratio. Moreover, TPHP disrupted mitochondrial ultrastructure of testicular Leydig cells and TM3 cells, reduced healthy mitochondria content and depressed mitochondrial membrane potential of TM3 cells, as well as inhibited mitochondrial fusion proteins mitofusin 1 (Mfn1), mitofusin 2 (Mfn2), and optic atrophy 1 (Opa1) expression, without effect on mitochondrial fission proteins dynamin-related protein 1 (Drp1) and fission 1 (Fis1) in testicular tissue and/or TM3 cells. Then, the mitochondrial fusion promoter M1 was used to pre-treat TPHP-exposed TM3 cells to determine the roles of mitochondrial fusion inhibition in TPHP-induced Leydig cells apoptosis. The results showed M1 pretreatment alleviated the above changes and further mitigated TM3 cells apoptosis and testosterone levels decreased, indicating TPHP induced TM3 cells apoptosis by inhibited mitochondrial fusion. Intriguingly, the intervention experiment of N-acetylcysteine (NAC) showed that TPHP-induced mitochondrial fusion inhibition is ROS dependent, because inhibition of ROS overproduction alleviated mitochondrial fusion inhibition, and subsequently relieved TPHP-induced apoptosis in TM3 cells. In summary, above data revealed that apoptosis is a specific mechanism for TPHP-induced male reproductive toxicity, and that ROS-mediated mitochondrial fusion inhibition is responsible for Leydig cells apoptosis caused by TPHP.